142k views
0 votes
The graph of y = cos⁡ x is transformed to y = a cos ⁡(x − c) + d by a vertical compression by a factor of 1/2 and a translation 3 units up. The new equation is:

Y = ½ cos (x + 3)

Y = 2 cos x + 3

Y = 2 cos x - 3

Y = ½ cos x + 3

User Mediobit
by
4.9k points

1 Answer

2 votes

Answer: Last Option


Y =(1)/(2)cosx + 3

Explanation:

If the graph of the function
y=kf(x) +d represents the transformations made to the graph of
y= f(x) then, by definition:

If
0 <k <1 then the graph is compressed vertically by a factor k.

If
|k| > 1 then the graph is stretched vertically by a factor k

If
k <0 then the graph is reflected on the x axis.

If
d> 0 the graph moves vertically upwards d units.

If
d <0 the graph moves vertically down d units.

In this problem we have the function
y = cos⁡x

And we know that The graph of
y = cos⁡x is transformed with a vertical compression by a factor of 1/2 and a translation 3 units up

therefore it is true that
0 <k <1 and
k=(1)/(2) and
d =3> 0

Therefore the new equation is:


Y =(1)/(2)cosx + 3

User Daerin
by
5.4k points